THE CORRELATION BETWEEN THE METABOLIC DISORDERS IN OBESE MEN AND THE BODY MASS INDEX (BMI) - Faour, Tarek; Hassan, Khodor Haidar; Atta-Alla, El Sayed S.; Prada, Edwin Parra; Nasreddine, Salam; Mcheik, Ali; Ghanem, Ricardos; Abdallah, Rony; Semaan, Pierre; Atta-Alla, Ahmed E.S.; et al. (European Scientific Journal, ESJ, 2015)
Background: The influence of body weight on serum lipids and uric acid is often overlooked in clinical practice. Objective: To study the magnitude of metabolic disorders (dyslipidemia and hyper-urecaemia) in asymptomatic obese men and its relation to body mass index (BMI). Methods: The study was conducted between September 2013 and July of 2014 at the medical analyses center in the Faculty of Public Health, Lebanese University. The weight, height, BMI, waist circumference (WC) uric acid, and lipid profile of 148 obese males, apparently healthy, compared with 80 males in a control group (BMI < 25 kg / mÂ²), were investigated. Subjects were grouped by BMI and WC in accordance with the National Institutes of Health cutoff points. Within the normal-weight (18.5-24.9), overweight (25.0-29.9), and obese (â‰¥ 30.0) BMI categories, we distributed the results of all the blood tests and we computed the prevalence of dyslipidemia and hyperurecaemia. Results: The present work revealed that with increasing body weight, the mean total cholesterol, LDL-C, triglycerides(TG), and uric acid increased; while the mean HDL-C decreased. These changes were as follows: the means difference between the first and second group and between the second and the third group were 29 and 31 mg/dl respectively regarding total cholesterol; for TG, these were 47.5 and 53.4 mg/dl; for LDL-C, these were 12 and 29 mg/dl; for HDL-C, these were 3.6 and 3.5 mg/dl; for uric acid, these were 0.3 mg/dl as a common difference, P=0.0245). Conclusion: Excess body weight is associated with deleterious changes in the lipoprotein profile and uric acid.